KARAKTERISTIK ALTERASI DAN MINERALISASI BERDASARKAN PENGAMATAN INTI BOR DENGAN METODE ANALYTICAL SPECTRAL DEVICES (ASD) DAN CORESCAN DI AREA PIT A DAN PIT C DAERAH TUMPANGPITU, KABUPATEN BANYUWANGI, JAWA TIMUR: ALTERATION AND MINERALIZATION CHARACTERISTICS BASED ON CORE LOGGING OBSERVATION WITH ANALYTICAL SPECTRAL DEVICES (ASD) AND CORESCAN METHODS AT PIT A AND PIT C AREA OF TUMPANGPITU, BANYUWANGI DISTRICT, EAST JAVA - Maftukha Alfiani; Dadan Wildan; Benny Bensalman; M. Hafid Rahadi; Trisna Suntara; Lia Novalia Agung (Buletin Sumber Daya Geologi, 2025)
The research area is located within the Mining Bussines Licence-Operation Production (IUP-OP) of PT Bumi Suksesindo in the Tumpangpitu area, Pesanggaran District, Banyuwangi Regency, East Java. The research area covers two areas, namely Pit A and Pit C. In Tumpangpitu, there are two types of ore deposits: porphyry copper and high-sulfidation epithermal gold. The aim of this research is to determine the types of lithology, alteration, mineralization, and ore deposit types in the research area. The research methods used include detailed core logging, analytical spectral devices (ASD) measurement, corescan, and mineragraphy analysis. The research was conducted using data from 10 drill holes: GTD-719, GTD-727, GTD-728, GTD-735, GTD-778, GTD-781, GTD-782, GTD-785, GTD-786, and GTD-792. The correlation results of the drill holes in the research area indicate that the lithology consists of andesite volcanic, preatomagmatic phase 1 breccia, dacite volcanic, diorite, preatomagmatic phase 2 breccia, and dacite intrusion dome. Based on the set of alteration minerals, pH, and temperature, there are 7 alteration zones: silica, silica ± alunite, pyrophyllite ± diaspore ± alunite, alunite ± pyrophyllite ± dickite ± kaolinite, alunite ± kaolin, kaolinite ± dickite ± montmorillonite-illite, chlorite ± montmorillonite-illite. The mineralization found includes pyrite (FeS₂), enargite (Cu₃AsS₄), and sphalerite ((ZnFe)S). The type of deposit in the research area is high-sulfidation epithermal deposit with a depth of 500-1,000 meters (intermediate).